THE INFLUENCE OF LIVE-STREAMING MARKETING TYPES ON THE BUYING INTEREST OF GENERAL Z CONSUMERS IN BUYING CLOTHES - Setiadi, Rafka Islaudyn Putra; Arafah, Willy (Universitas Negeri Makassar, 2026)
Abstract: Advances in digital technology have driven the emergence of innovative marketing strategies, one of which is live-streaming marketing, which is now widely adopted in the fashion industry. This research explores howProfessional Live-streaming MarketingAndEntertainment Live-streaming Marketinginfluence Gen Z's desire to purchase fashion products. This study also examines whetherSocial Influence Mechanismplays a role in this relationship. Data was collected from 122 Gen Z individuals (18-26 years old) in Greater Jakarta who watchedlive-streaming fashion, with analysis conducted using SEM. The findings show that both types of live streaming positively influence Purchase Intention. Most importantly,Social Influence Mechanismwas found to be a key mediator. This implies that fashion brands should combine useful information with engaging content and encourage interaction to increase Gen Z purchases.Keywords: Live Streaming Marketing, Social Influence Mechanism, Purchase Intention, Gen Z